2021
DOI: 10.1108/jarhe-04-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

The predictive validity of entrance scores and short-term performance for long-term success in engineering education

Abstract: PurposeThis study examined predictors of cumulative grade point average (GPA) from entrance scores and successive performance during students' academic work in university engineering programs.Design/methodology/approachScores from high school coursework, the General Ability Test and the Achievement Test were examined to determine if these factors and annual successive GPAs were predictors of long-term GPA. The sample consisted of 2,031 students registered in university engineering programs during the 2013–2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The observed relationship between Grade Point Average and Cumulative Grade Point Average on the academic achievement of students was studied by Abdelfattah et al, 17 Abdulkadir and Ogwueleka, 19 Lawal et al, 20 Debaliz et al, 24 Almarabheh et al, 25 Oguntunde et al, 23 the researchers concluded that GPAs have a strong linear relationship with final year CGPA of students. We anticipate to have similar findings in this study.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The observed relationship between Grade Point Average and Cumulative Grade Point Average on the academic achievement of students was studied by Abdelfattah et al, 17 Abdulkadir and Ogwueleka, 19 Lawal et al, 20 Debaliz et al, 24 Almarabheh et al, 25 Oguntunde et al, 23 the researchers concluded that GPAs have a strong linear relationship with final year CGPA of students. We anticipate to have similar findings in this study.…”
Section: Introductionmentioning
confidence: 98%
“…Abdelfattah et al, 17 conducted a predictive validity study on entrance scores and short‐term performance for long‐term success in Engineering Education. The study examined the effect of high school coursework, general ability tests, and achievement tests on CGPA.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, GPAs have not only been used as predictors of success, but also as outcome measures; e.g., measures of academic success in higher education 8,9 . It is argued that this further conflicts attempts to develop predictive models of success.…”
Section: Introductionmentioning
confidence: 99%